McArdle Disease and Pregnancy - João D Melo; Bráulio Gomes; José P Leite; Mercedes Agúndez (Sociedade Galega de Medicina Interna, 2015)
McArdle disease (Glycogen Storage Disease type V) is a rare hereditary disease, frequently diagnosed in adulthood. It is associated with exercise intolerance and severe rhabdomyolysis. There are only a few reported cases of pregnancy in these patients, and in most of them there was no worsening of the disease. The authors report the case of a young woman presenting with severe rhabdomyolysis by the age of 28, being diagnosed with McArdle. She complained about exercise intolerance since childhood, but never had valued these symptoms. The authors also describe two pregnancies in the same patient. During the first pregnancy, there was improvement of the patient's complaints, but it was not observed during the second one. The basis of the therapy of this disease consists of aerobic exercise and ensuring euglycaemia and enough protein intake. With these measures, it is possible to control the symptoms and complications of the disease.